2008
DOI: 10.1016/j.molcel.2008.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Drug-Dependent Ribosome Stalling

Abstract: Inducible expression of the erm erythromycin resistance genes relies on drug-dependent ribosome stalling. The molecular mechanisms underlying stalling are unknown. We used a cell-free translation system to elucidate the contribution of the nascent peptide, the drug, and the ribosome toward formation of the stalled complex during translation of the ermC leader cistron. Toe-printing mapping, selective amino acid labeling, and mutational analyses revealed the peptidyl transferase center (PTC) as the focal point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
334
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 247 publications
(364 citation statements)
references
References 54 publications
22
334
1
7
Order By: Relevance
“…Previous analysis of the regulatory leader peptides of erythromycin resistance rRNA methyltransferase (erm) genes showed that macrolide-dependent programmed translation arrest depends on the sequence of the nascent chain preceding the stall site (8,(12)(13)(14)(15)19). Recent structural studies revealed that out of the C-terminal amino acids of the stalled nascent peptide, residues −8 to −2 (if the C-terminal residue is assigned position number 0) are in close proximity to the NPET-bound macrolide antibiotic (14,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of the regulatory leader peptides of erythromycin resistance rRNA methyltransferase (erm) genes showed that macrolide-dependent programmed translation arrest depends on the sequence of the nascent chain preceding the stall site (8,(12)(13)(14)(15)19). Recent structural studies revealed that out of the C-terminal amino acids of the stalled nascent peptide, residues −8 to −2 (if the C-terminal residue is assigned position number 0) are in close proximity to the NPET-bound macrolide antibiotic (14,20).…”
Section: Resultsmentioning
confidence: 99%
“…Some biochemical evidence argues that the action of macrolide antibiotics depends on the properties of the polypeptide being synthesized by the drug-bound ribosome as revealed by differential inhibition of in vitro translation of certain model and natural mRNA templates (8)(9)(10). Consistent with these observations, the sites of macrolide-induced programmed ribosome stalling at the regulatory leader ORFs, which control expression of the macrolide resistance genes, are defined by the sequence of the encoded nascent peptide (11)(12)(13)(14)(15). Importantly, the protein-specific action of macrolides is readily observed in vivo, because treatment of sensitive cells with even very high concentrations of antibiotics allows the continued production of a subset of cellular polypeptides (8).…”
mentioning
confidence: 90%
“…3C). Similarly, minute modifications in the structure of the antibiotics or in their binding sites may have significant effects on their binding and properties (20,37,54,55). LM on its own is a less potent protein synthesis inhibitor than ERY.…”
Section: Discussionmentioning
confidence: 99%
“…Although either of these mechanisms are feasible, we favor the second possibility, which is consistent with our findings that blocking efflux with PA␤N makes cells more sensitive to erythromycin and deleting either the AcrA/AcrB or TolC components of the AcrAB-TolC efflux pump reduces the erythromycin resistance of a strain with ⌬MKR-L22-titin ribosomes compared with a strain with L22-titin ribosomes. The ⌬MKR mutation is known to affect translation of certain mRNAs by reducing programmed ribosome stalling (36,37). How might ⌬MKR-linked translational changes affect macrolide uptake or efflux?…”
Section: Discussionmentioning
confidence: 99%